Amine oxidase from Euphorbia characias: Kinetic and structural characterization. (23rd October 2017) - Pintus, Francesca; Sabatucci, Annalaura; Maccarrone, Mauro; Dainese, Enrico; Medda, Rosaria
Abstract: This minireview focuses on a plant copper/2, 4, 5‐trihydroxyphenyl alanine quinone amine oxidase isolated from the latex of the shrub Euphorbia characias (ELAO). This enzyme has been investigated in terms of both molecular structure and kinetic mechanism. The characterization of this enzyme allowed us to identify specific amino acids and domains that play a key role in modulating substrate access into the active site not only for ELAO but also for other plant and mammalian amine oxidases. As mammalian amine oxidases are implicated in several physiological and pathological conditions, the deep structural characterization of their active site accession mechanisms could be the starting point for the development of enzyme modulators with high therapeutic potential. Thus, this paper gives structural/functional insights that open new perspectives in the research about the whole amine oxidase family.